Regulation and recovery of sink strength in rice plants grown under changes in light intensity - Lafarge, Tanguy; Seassau, Célia; Martin, Meryll; Bueno, Crisanta; Clément-Vidal, Anne; Schreck, Eva; Luquet, Delphine (Commonwealth Scientific and Industrial Research Organisation, 2010)
The aim of this study was to characterise the sequence of traits that influence the response of rice morphogenesis to a shortage in carbohydrate supply and to its recovery. Plants were grown under 70% shading or full-light exposure for distinct periods during the vegetative and early reproductive phases in field and controlled environments. Lower organ vigour (i.e. higher specific leaf area and specific stem length), sugar concentration, tiller emergence and leaf elongation rate; higher leaf blade to sheath length ratio and preferential assimilate allocation to sink (elongating) leaves, were observed soon after the onset of shading. Organ vigour was affected before any appreciable effect on tiller emergence was noted. All the processes resumed after the shading removal, which coincided with a boost in sugar concentration; however, the extent of recovery in organ vigour and tillering depended on the growth stage at which shading was applied. It is concluded that crop response to changes in carbohydrate supply at the early stage favoured leaf area production by adjusting transient reserve levels and biomass allocation. Results of this study provide further insights into the role of soluble carbohydrates in plant and crop phenotypic plasticity and, thus, into the value of such processes in plant growth models.